Kultur Jaringan Jeruk Keprok Tejakula (Citrus reticulata var. Tejakula) Menggunakan Tunas Muda dan Biji Serta Deteksi CVPD dengan Teknik Polymerase Chain Reaction (PCR) - SIPANGKAR, VLORA VERONICA; WIJAYA, I NYOMAN; SRITAMIN, MADE (Agrotrop : Journal on Agriculture Science; Vol 10 No 1 (2020), 2020)
Tissue Culture Citrus ( Citrus reticulata var. Tejakula) using Shoot and Seed and the Detection of CVPD with Polymerase Chain Reaction (PCR). The sample was taken in Pecatu Village, Kuta Selatan District, Badung Regency and continued with in vitro culture and PCR analysis at UPT. Genetic Resource and Molecular Biology Laboratory, was start from  December of 2018 until May of  2019. The purpose of this research was to create a CVPD free Citrus reticulata var. Tejakula seedling from tissue culture. The sample was chosen based on visual characteristic. Two samples were taken from  citrus  plant  that  show  CVPD  symptoms  and  citrus  plant  that  did  not  show  CVPD symptoms. The seed  and shoot  were cultured using MS media for 12  week after planting (WAP). From this research showed that both explant from the shoot and seed were able to grow well.  The  explant  from  citrus  sample  that  showed  CVPD  symptoms  was  infected  by Liberibacter asiaticus and the explants from citrus that did not show CVPD symptoms was not invected by Liberibacter asiaticus, according to PCR analysis.